Exploration into Plasma Hsa_circ_0052184 as a New Biomarker of Colorectal Cancer Prognosis - Zheng E; Xiao D (Dove Medical Press, 2023)
Enqi Zheng, Deshuang Xiao Hernia Vascular Surgery, The First People's Hospital of Wenling, Wenling, Zhejiang, People's Republic of ChinaCorrespondence: Deshuang Xiao, Hernia Vascular Surgery, The First People's Hospital of Wenling, No. 333 Chuan'an South Road, Chengxi Street, Wenling, 317599, Zhejiang, People's Republic of China, Tel +86-057689668595, Email xiaodeshuang456@126.comBackground: Circular RNAs (circRNAs) are strong modulators of tumor pathology. Herein, our goal was to examine the plasma hsa_circ_0052184 content among colorectal cancer (CRC) patients, and assess its association with patient clinicopathological profile and diagnostic values.Methods: Overall, we collected 228 presurgical CRC and 146 normal plasma samples from The First People's Hospital of Wenling. Circulating hsa_circ_0052184 levels were assessed via qRT-PCR, and the diagnostic prediction was conducted with the receiver operating characteristic (ROC) curve.Results: Relative to healthy controls, CRC patients exhibited markedly enhanced circulating hsa_circ_0052184 levels, which were closely correlated with advanced stage of disease and worse outcome. Based on our uni- (UA) and multivariate assessments (MA), elevated hsa_circ_0052184 levels were a stand-alone predictor of poor prognosis. The ROC curve depicted an area under the curve (AUC) for CRC diagnosis to be 0.9072.Conclusion: Circulating hsa_circ_0052184 is a potential bioindicator of CRC outcome.Keywords: hsa_circ_0052184, diagnostic biomarker, colorectal cancer